FINANCIAL PERFORMANCE IN SRI KEHATI COMPANY - Rosita Wulandari (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to determine and obtain empirical evidence about the influence of capital structure and ownership structure that is proxied by managerial ownership and institutional ownership on the company's financial performance with firm size as a control variable on companies listed on the Indonesia Stock Exchange and included in the SRI-KEHATI Index period 2013-2018. In this study researchers used quantitative research types. And the method used in this study is the associative method, with a total sample of 42 samples from 7 companies selected using purposive sampling techniques based on predetermined criteria. The data used are secondary data in the form of financial statements that have been audited from 2013 to 2018 taken from the Indonesia Stock Exchange website. Data analysis techniques used are descriptive statistics, classic assumption tests, and hypothesis testing. The results showed that: capital structure has a negative and significant effect on the company's financial performance, ownership structure that is proxied by managerial ownership has a positive and significant effect on the company's financial performance, ownership structure that is proxied by institutional ownership has a negative and significant effect on the company's financial performance. And the results of the research on capital structure and ownership structure proxied by managerial ownership and institutional ownership, and the size of the company influence the company's financial performance.